7y-1=2(y+3-2)

Simple and best practice solution for 7y-1=2(y+3-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-1=2(y+3-2) equation:


Simplifying
7y + -1 = 2(y + 3 + -2)

Reorder the terms:
-1 + 7y = 2(y + 3 + -2)

Reorder the terms:
-1 + 7y = 2(3 + -2 + y)

Combine like terms: 3 + -2 = 1
-1 + 7y = 2(1 + y)
-1 + 7y = (1 * 2 + y * 2)
-1 + 7y = (2 + 2y)

Solving
-1 + 7y = 2 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
-1 + 7y + -2y = 2 + 2y + -2y

Combine like terms: 7y + -2y = 5y
-1 + 5y = 2 + 2y + -2y

Combine like terms: 2y + -2y = 0
-1 + 5y = 2 + 0
-1 + 5y = 2

Add '1' to each side of the equation.
-1 + 1 + 5y = 2 + 1

Combine like terms: -1 + 1 = 0
0 + 5y = 2 + 1
5y = 2 + 1

Combine like terms: 2 + 1 = 3
5y = 3

Divide each side by '5'.
y = 0.6

Simplifying
y = 0.6

See similar equations:

| 2-1(x-1)=13 | | -2(3x+9)+5(2x+3)=-39 | | 6x^2+3x-108=0 | | 2(w+3)-6w=-14 | | 2*6*3= | | =5*8 | | 5+3p=19 | | 4(5x+7)-(3-x)=4 | | 2n-n+5=3 | | 10+3-(8)= | | w+2x-3y+5y=-98 | | 30-9(5x+1)=-24 | | 5m=8-23m | | -(4a-8)=2(a+4) | | -30=-5x-15 | | x+4*3=x+18 | | 33%x+6=12 | | -4n+6=-3n+8+4 | | 30-9(5x+1)=24 | | 4x^2-32x+52=0 | | -8+x=11 | | -16x-15=14x-23 | | x=6+-15 | | 7x+8=3x+44 | | -3(2+4p)=2(2p-1) | | 8-11=7k | | -4x-12=36 | | -24-f=-15 | | 4x+7=5x-x-1 | | 2(3-3x)+4=-6(-8+2x)-2 | | 6x^2+7xy+3y^2=144 | | 5log+10=7m |

Equations solver categories